2020
DOI: 10.1038/s41372-020-00783-z
|View full text |Cite
|
Sign up to set email alerts
|

Inadequacies of hospital-level critical congenital heart disease screening data reports: implications for research and quality efforts

Abstract: Objective: Assess the quality of critical congenital heart disease (CCHD) screening data reports in California, where CCHD screening is not mandatory but reporting is. Study Design: Retrospective review of California hospital-level CCHD screening data to evaluate data reliability and adherence to state screening and reporting recommendations. Data were evaluated for internal consistency and compared to two databases. Results: Over one-third o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We leveraged the EMR data-base to create insights across all EHS facilities. Since the Screening order is an automated order through the EMR, we found that the compliance with screening for all new-borns was higher (99%) than in some other systems around the world [ 27 ]. Utilizing EMR to prompt guideline adherence to end-users has proven an effective strategy in many settings [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…We leveraged the EMR data-base to create insights across all EHS facilities. Since the Screening order is an automated order through the EMR, we found that the compliance with screening for all new-borns was higher (99%) than in some other systems around the world [ 27 ]. Utilizing EMR to prompt guideline adherence to end-users has proven an effective strategy in many settings [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review of congenital heart disease screening reports in California found that over one-third of hospitals did not submit data – in spite of reporting being mandatory – and only 46% of reporting hospitals submitted data with matching numbers of completed screens and results. 20 A study of completeness and correctness of growth charts in Ghana found that more than two-thirds were not filled out completely and 26% were not filled out correctly. 21 A study of vaccination coverage measurement in 194 World Health Organisation member states found many inconsistencies in data quality, concerning completeness of reporting and implausible values.…”
Section: Discussionmentioning
confidence: 99%
“…An unexpected situation was observed in California, the only state where POx screening is offered but not mandated, and reporting to state agencies is required. 45 Compliance to reporting was poor, with one third of California's hospitals 46 not submitting screening data to the state and less than half submitting data matching the number of screens. Yet, state respondents demonstrated a higher policy consistency than those from nonreporting states, perhaps since a reporting requirement may increase accountability.…”
Section: Discussionmentioning
confidence: 99%